Recent Trends in Therapeutic Radiopharmaceuticals - Chandan B Jha; Nidhi Jain; A K Pathak (Current Research in Pharmaceutical Sciences, 2016)
Radiopharmaceuticals have been majorly used in ages for the diagnostic agent and therapeutic agents .Recent years enormous efforts have been made to formulate holistic formulation for the therapeutic effect of Radiopharmaceuticals .Due to its versatile applications in cancer , Theraspheres -which are glass beads microparticals containing yttrium 90 isotope as a therapeutic agents for Osteosarcoma and its liposomes containing yttrium 90 for the treatment of throat and neck cancer have been formulated .These new formulations have added a new dimension in the field of Research and Development .This review explains need of Radiopharmaceuticals ,their advantages over conventional drug delivery systems and there different application in pharmaceutical fields.